Take Hold of a New Dow Plastic - Dow Chemical Company (1945)
Color print advertisement for Styraloy and other plastics manufactured and sold by the Dow Chemical Company. The advertisement features an illustration of a hand holding a screwdriver, with accompanying text detailing the flexibility, durability, and sturdiness of materials made from Styraloy and other Dow plastics.
Keywords: Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Advertising; Advertising, Industrial